Study of echocardiography findings in patients with type II diabetes mellitus - Shrestha, Apurba; Dhungel, Sanjib (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Diabetes mellitus is an escalating public health problem globally. Cardiovascular disease is the major cause of morbidity and mortality among patients with diabetes. Diabetes mellitus is an established risk factor for congestive cardiac failure in which the diastolic function is impaired more than the systolic function.Method: A cross-sectional study was conducted from 2018 to 2019. The sample size of the study was 60 respondents. An independent student t-test and a chi-square test were used to test the statistical significance between the two variables (with two categories) in quantitative and qualitative variables respectively. Significant results were defined as p-values less than 0.05 at 95% confidence intervals.Result: Left ventricular diastolic dysfunction (LVDD) was found in 36 (60%) of the patients. Left ventricular systolic dysfunction (LVSD) was found in 11 (18.3%) of the patients. The correlation between LVDD and index of glycemic control i.e. HbA1c was statistically significant (P value 0.025). It was also found that prevalence of LVDD increased with the duration of diabetes (P value 0.007), also the frequency of LVSD increased with duration of diabetes (P value 0.009).Conclusion: LVDD was more common in diabetic patients with poor glycemic control and prolonged duration of the disease. LVSD was less common in diabetic patient in comparison with LVDD, but the frequency of LVSD also increased as the duration of diabetes progressed.